2014
DOI: 10.1111/gcb.12564
|View full text |Cite
|
Sign up to set email alerts
|

Elevated carbon dioxide and ozone alter productivity and ecosystem carbon content in northern temperate forests

Abstract: Three young northern temperate forest communities in the north-central United States were exposed to factorial combinations of elevated carbon dioxide (CO2) and tropospheric ozone (O3) for 11 years. Here, we report results from an extensive sampling of plant biomass and soil conducted at the conclusion of the experiment that enabled us to estimate ecosystem carbon (C) content and cumulative net primary productivity (NPP). Elevated CO2 enhanced ecosystem C content by 11%, whereas elevated O3 decreased ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 69 publications
(184 reference statements)
1
61
0
2
Order By: Relevance
“…However, some studies have found that O 3 can decrease soil carbon content. Talhelm et al (2014), for example, found O 3 reduced carbon content in near surface mineral soil of forest soils exposed to 11 years of O 3 fumigation. Hofmockel et al (2011) found elevated O 3 reduced the carbon content in more stable soil organic matter pools, and Loya et al (2003) showed that the fraction of soil carbon formed in forest soils over a 4-year experimental period when fumigated with both CO 2 and O 3 was reduced by 51 % compared to the soil fumigated with CO 2 alone.…”
Section: Impacts Of O 3 At the Land Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have found that O 3 can decrease soil carbon content. Talhelm et al (2014), for example, found O 3 reduced carbon content in near surface mineral soil of forest soils exposed to 11 years of O 3 fumigation. Hofmockel et al (2011) found elevated O 3 reduced the carbon content in more stable soil organic matter pools, and Loya et al (2003) showed that the fraction of soil carbon formed in forest soils over a 4-year experimental period when fumigated with both CO 2 and O 3 was reduced by 51 % compared to the soil fumigated with CO 2 alone.…”
Section: Impacts Of O 3 At the Land Surfacementioning
confidence: 99%
“…In the Feng et al (2008) meta-analysis of wheat, O 3 reduced aboveground biomass (−18 % at a mean O 3 concentration of 70 ppb) photosynthetic rate (−20 % at a mean O 3 concentration of 73 ppb) and g s (−22 % at a mean O 3 concentration of 79 ppb). One of few long-term field-based O 3 exposure studies (AspenFACE) showed that after 11 years of exposing mature trees to O 3 (mean O 3 concentration of 46 ppb), O 3 decreased ecosystem carbon content (−9 %) and decreased NPP (−10 %), although the O 3 effect decreased through time (Talhelm et al, 2014). Zak et al (2011) showed this was partly due to a shift in community structure as O 3 -tolerant species, competitively inferior in low-O 3 environments, outcompeted O 3 -sensitive species.…”
mentioning
confidence: 99%
“…the range for the FACE experiments, which typically increase CO 2 from ~370 to ~550 ppm) ( Figure 1). Furthermore, S15's synthesis of FACE data is incomplete as it omits several years of published data 13,14 , and incorrectly estimates an overall effect size by taking the median across experiments, species and years, rather than calculating a more appropriate response ratio 15 .…”
mentioning
confidence: 99%
“…In experimental forests, O 3 reduced the C content in woody tissues and in the near‐surface mineral soil (Talhelm et al., 2014), and in more stable SOM pools (Hofmockel, Zak, Moran, & Jastrow, 2011), but data from a high‐elevation grassland experiment indicated that soil C remains unchanged, possibly because a low C input was compensated by reduced turnover (Volk et al., 2011), as discussed above. Similarly, in a modeling study, the replacement of sensitive by more tolerant plant species or genotypes (as also discussed above) in a temperate deciduous forest led to unchanged biomass C stocks in the long term (>100 years) (Wang, Shugart, Shuman, & Lerdau, 2016).…”
Section: Implications For Terrestrial Feedbacks To the Atmospherementioning
confidence: 99%